ANALISIS IMPLEMENTASI KEBIJAKAN PENCEGAHAN DAN PENANGGULANGAN HIV/AIDS PADA GAY DI KABUPATEN BANYUWANGI - Pratama, Ananda Horizki; Priyanto, Hary; Hentika, Niko Pahlevi (JURNAL KATARSIS, 2024)
Analysis Of Policy Implementation Of HIV/AIDS And Control On Gay In Banyuwangi District.  This research was conducted to determine the implementation of HIV/AIDS prevention and control policies in Banyuwangi Regency. The HIV/AIDS status in Banyuwangi Regency is getting higher and is ranked second in East Java as an HIV/AIDS red zone. Cases of HIV/AIDS There are still many sufferers, for example cases that are often found in Banyuwangi Regency are people with HIV/AIDS in gay people.  This study uses a qualitative method with a descriptive perspective, using observation data collection techniques, guided free interviews, and documentation. In the implementation of HIV/AIDS prevention and control policies for gays in Banyuwangi Regency, using the theory of William Dunn (2004) which focuses on 5 (five) aspects, namely: Policy Problems;  The Future of Policy;  Policy Action;  Policy Results;  and Policy Performance.  The result of the research is that the Health Office along with KPA and other stakeholders have made efforts to control HIV/AIDS in Banyuwangi Regency, as has been written in the policy through Perda Number 5 of 2017. Namely gay, in the end not all certain communities can know the existence of regulations made by the government and have limited socialization and awareness of certain communities so that the existence of Regional Regulation Number 5 of 2017 is only limited to written regulations.